Pengaruh Motivasi Kerja Dan Pelatihan Terhadap Kinerja Karyawan Di Mal Pelayanan Publik Kabupaten Maros Sulawesi Selatan - Muh Fauzan Rizaldy Yusuf; Andi Heru Susanto (Jurnal Manajemen Riset Inovasi, 2024)
Technology and globalization have triggered increasingly fierce competition in the workplace, including in local government, such as Maros Regency. In the context of public service, improving employee performance is crucial, especially at the Public Service Mall, to provide effective services to the community and achieve competitive advantage. This study aims to analyze the influence of motivation and training on employee performance. The research method used is an associative quantitative approach involving 100 respondents. The research instrument was a questionnaire that had been tested for validity and reliability. Data analysis was conducted using descriptive analysis and correlation, while hypothesis testing was carried out using multiple linear regression analysis. The results showed a negative influence of motivation and training on employee performance with an R-Square value of 0.114. The limitation of this study lies in its scope, which only covers one government office in Maros Regency and does not consider other variables or moderators that may affect employee performance more comprehensively.